STUDENTS’ ABILITY IN USING SUBJECT VERB AGREEMENT IN WRITING AN ESSAY - Nur Izzah Dinillah; Nunung Anugrawati; Ariana (FKIP Unismuh Makassar, 2021)
This study aimed at finding out how the students' skills in using subject-verb agreement in writing essays. This research method is descriptive quantitative method. The research data was collected through the writing test as an instrument. The sample of this research was the fifth-semester students of English Education at the Alauddin State Islamic University of Makassar. The sample was taken by using simple random sampling. Based on the analysis and discussion about this research, the researcher concluded the researcher concluded that the students' ability to use the subject-verb agreement in the fifth semester students of English Education at the Alauddin State Islamic University of Makassar was categorized into very good level with a score was 88.24. This value is obtained based on the results of the scores of all students that are divided into the number of students who are the samples of this study. From 35 students, there were 7 students whose mastery levels were excellent, 16 students gained a very good level, 8 students whose mastery levels were good, 3 students gained a good level, 1 student gained a fair level, and no student gained a poor level. Moreover, the last level is very poor and no student gained this level.